FEATURES OF HOUSING AND HOUSEHOLD CULTURE OF THE DON MINERS IN THE SECOND HALF OF THE XIX CENTURY - N. Manukovskiy (Гуманитарные и юридические исследования)
The article is devoted to the little-studied question about the features of housing and household culture of the Don miners in the post-reform period. A number of issues related to the values and attitudes of miners in the housing sector, their needs and living standards are considered. During the period under review, the vast majority of Don miners lived in dugouts and cabins. In some cases, the miners refused to move from the dugouts to comfortable premises. During the 1860-80-ies miners did not put forward demands for improvement of living conditions during protests. These facts give the basis to claim that the bulk of miners differed unpretentiousness in the housing and household sphere, readiness to put up with household disorder. Among some of the miners, this homely simplicity was due to the fact that they worked seasonally and looked at their home in the mines as temporary. At the same time, at the beginning of the post-reform period at mines of Don the full-fledged houses constructed by miners began to appear that testiies to emergence among them a layer of workers with higher household needs and living standards. Also, some miners, hunters earned in the mines money to build brick or stone houses in their native villages. During the 1890s, most of the Don miners (about 90%) were relocated from dugouts to large stone barracks and houses from the enterprise. However, it should be noted that the resettlement of 90% of miners from dugouts to barracks and family houses was solely on the initiative of enterprises, which also conirms their everyday unpretentiousness.